Moon in the Poetry of Misak Metsarents and it’s Lingual-stylistic Features - Arakelyan, K. L.
Celestial bodies, luminaries and phenomena have accompanied mankind since time immemorial. Heavenly luminaries have been an inexhaustible source of inspiration for poets. Creators praised creation, marveled at the beauty of luminaries, perceived man as a part of nature and in inseparable connection with all other elements. Heavenly bodies and phenomena have often served as a way to reveal the inner world of a person, his past path, hopes and expectations for the future. In this sense, Western Armenian lyric poetry of the beginning of XX century is not an exception. The mentioned topic received remarkable comments in the work of Siamanto, Daniel Varoozhan, Ruben Sevak, especially Misak Metsarents. Celestial bodies, luminaries and phenomena are a significant number in Metsarents’ poetry have a great stylistic role. One of these the noun moon and its various synonyms, which very often become the core and body of the poetic image, endow the speech with incomparable nuances, beauty and originality, causing the reader the greatest aesthetic pleasure, transporting him to an extraterrestrial light sphere.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture